Exploração sexual de menores e o papel da instituição escolar - Rebolho, Ana Claudia Figueiredo [UNESP]; Fernandes, Silvia Aparecida de Sousa [UNESP] (My University, 2012)
Prostitution is an activity that generates constant conflict and controversy. The way it is practiced leads, in some specific situations, the legal framework. For the analysis of the role of school and sex education, this research aimed to: identify and analyze the views of managers and teachers living with sexual exploitation of children in two schools in the state schools of a city of the State of São Paulo and to determine whether the subject is part of school curricula in the schools surveyed and discussed how teachers. The research is part of qualitative research in education and had the strategy of data collection a questionnaire with managers and teachers of educational institutions surveyed. The data collected and analyzed showed that the school, being a place that works with multiculturalism is that, as a place where the "Sex Education" should be worked out, mainly to educate their students not to enter the world of sexual exploitation. Therefore, the school is the place for fundamental change in mentality of children and adolescents who are forced to surrender to sexual exploitation.

A prostituição é uma atividade que gera constantes conflitos e controvérsias. A maneira como é praticada acarreta, em algumas situações específicas, enquadramento legal. O trabalho é resultado de uma pesquisa de mestrado que objetivou analisar as concepções de gestores e professores que convivem com a Exploração Sexual de Menores, em duas escolas da rede estadual de ensino de um município do interior do Estado de São Paulo. Objetivou, também, identificar se o tema exploração sexual de menores faz parte dos currículos escolares nas escolas pesquisadas e como é abordado pelos professores. Trata-se de uma pesquisa qualitativa em educação. Utilizou-se como estratégia de coleta de dados a aplicação de questionário com gestores e professores das instituições de ensino pesquisadas. Identificou-se que os docentes raramente abordam a temática estudada em suas aulas e afirmam sentir-se despreparados para este trabalho. Conclui-se que a escola é um lugar privilegiado onde a Educação Sexual deve ser trabalhada, principalmente no sentido de educar seus alunos a não adentrar no mundo da exploração sexual.
Sexual exploitation of children and the role of the school
Keywords: exploração sexual de menores; Educação básica; instituições escolares